Fan Sentrifugal Untuk Pembuangan Gas Hasil Pengelasan Laboratorium Teknologi Produksi Fakultas Teknik Universitas Riau - Hutasoit, Topo Ali; Asral, Asral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The fan centrifugal for exhaust of welding gas has developed to ensure the welder in healthy from the effect of welding gas emition. The purpose of this study was measure the amount of gas in order to know suitable position and space in welding proces. Testing done with variation of distances, positions and the production of smoke. The testing have conducted in horizontal and vertikal positions. The positions are 10 cm, 20cm, 30 cm from the center of pipe suction. Respectively the diameter of welding electrodes are 2.6 mm, 3.2 mm, 4.0 mm. The fan centrifugal is able to exhaust the gases of welding it look there is no gases left after welding process in the end. Then the best position has 20 cm from the centre of pipe suction with vertical positionKey Word : exhaust fan centrifugal, impeller, welding gas emition